Foreign direct investment in Macedonia – Is there discrimination in practice? - Petrevska, Biljana (Association of Economists and Managers of the Balkans, Belgrade, Serbia, 2018)
The subject of research of this paper presents the foreign direct investment in the Republic of Macedonia. The purpose of the research of this paper is to show whether there is discrimination between domestic investment in the Republic of Macedonia and foreign investments in the country. The first part is an introduction which explains the topic of the research, while the second part focuses on the legal and institutional framework for foreign direct investment in the Republic of Macedonia. The third part of the paper explains the conditions for attracting foreign direct investment in the Republic of Macedonia. The fourth part of the paper analyzes and gives answers for the discrimination between foreign and domestic investment in the practice of the country. Finally, the fifth part of the paper is the conclusion.
Keywords: investment, domestic investment, foreign direct investment, portfolio investment, discrimination